Sport and exercise psychology : the key concepts - 506014 Cashmore, Ernest; Cashmore, Ernest. Sport psychology (London, ENK. ; New York : Routledge, 2008)
"Now including exercise psychology terms for the first time in its new edition, Sport and Exercise Psychology: The Key Concepts offers a highly accessible introduction to this subject, its central theories and state-of-the-art research. Over 300 alphabetically-ordered entries cover diverse terms." "Cross-referenced, with suggestions for further reading and a full index, this latest key guide contains invaluable advice on the psychology of Sport and Exercise. A comprehensive A-Z guide to a fast-moving field of inquiry, this book is an essential resource for scholars, coaches, trainers, journalists, competitors, exercisers; in fact anyone associated with sport and exercise."--BOOK JACKET.